Neither Gametes nor Children. Italian Prospective Parents and the Variable Meaning of Donor Embryos - Zanini, Giulia (Tecnoscienza – Italian Journal of Science & Technology Studies, 2013)
“Sperm donation”, “egg donation”, “double donation”, “embryo donation” and “embryo adoption” are the main terms that prospective parents in Italy employ to refer to donor reproductive practices, which are forbidden within Italian national territory since 2004. Italian residents who think of donated gametes or embryos as viable ways to parenthood currently need to address assisted reproduction centres abroad. Drawing on a four-year ethnographic research on Italian cross-border reproductive travellers approaching donor conception, this paper aims at investigating the ways in which prospective parents choose and make sense of different kind of donation practices that consist in the use of donor embryos and explores their understanding of such practices with reference to the notions of personhood and parenthood in a context of transnational reproduction. In particular, this paper explores how they make sense of different “histories” of embryos, included the way in which reproductive cells have changed owners according to different trajectories.